(untitled) (Analysis in Theory and Applications, 2023)
Let (X, d) be a cone metric space and T : X → X be a mapping. In this paper, we shall introduce the concept of strong T-stability of fixed point iteration procedures with respect to T in cone metric spaces. Also, we will investigate some meaningful results on strong T-stability of Picard iterations in cone metric spaces without the assumption of normality. Our main results improve and generalize some related results in the literature.